In Vivo Bioconcentration, Distribution and Metabolization of Benzophenone-3 (BP-3) by Cyprinus carpio (European Carp) - Florentina Laura Chiriac; Irina Eugenia Lucaciu; Iuliana Paun; Florinela Pirvu; Stefania Gheorghe (Foods, 2022)
Organic UV-filters, such as oxybenzone (BP-3), have attracted researcher attention in recent years due to its capacity to interfere with the proper functioning of the endocrine system and its widespread presence in the aquatic environment. The aim of this study was to investigate the bioconcentration, distribution and metabolization of BP-3 in one of the most common fish species in Romania, namely Cyprinus carp (European carp). Exposure experiments were performed for 11 weeks using a BP-3 nominal concentration level of 100 µg/L. The BP-3 concentration level decreased over time and needed to be re-established daily. Biological samples (fish organs and tissues) from control and test were taken at t0 (before contamination) and at t3, t5, t8 and t11 weeks from the beginning of the experiment. From the third week, BP-3 was identified and quantified, in all organs, in concentration values ranging between 3.2 and 782 ng/g d.w., the highest concentration being detected in the intestinal content, followed by gonads (up to 468 ng/g d.w.) and skin (up to 453 ng/g d.w.). In the case of gill and liver, the BP-3 concentration increased in the first five weeks, and then decreased to 15 and 6 ng/g d.w., respectively, which could be explained by a fast BP-3 metabolization. During the exposure period, six metabolites were identified through LC-MS/MS, all of them known for their endocrine disruptor and toxic properties being higher than those of the parent compound. The study is important from an ecological perspective and also in view of human health concerns involving food quality.